Analysis of Bone Fracture Detection Based on Harris Corner Detector Method - Bahrun Niam; Imam Much Ibnu Subroto; Sri Arttini Dwi Prasetyowati (Journal of Telematics and Informatics, 2018)
Bone is part of the human body to sustain other parts of the body. One of the bones is leg bone. Leg bones have often cracks or fractures caused by collision. Leg bone fractures can be identified by using x-ray manually. Eye train can cause less accurate in identifying the result of roentgen so that it needs a method to make radiologist easier in determining leg bone fractures. The recommended method in this research was Harris corner detector method. Before identified, the object was firstly in pre-processing such collecting data, grayscale and cropping image. The research result was Harris corner detector method could identify leg bone fractures with 70% accuracy. Bone is part of the human body to sustain other parts of the body. One of the bones is leg bone. Leg bones have often cracks or fractures caused by collision. Leg bone fractures can be identified by using x-ray manually. Eye train can cause less accurate in identifying the result of roentgen so that it needs a method to make radiologist easier in determining leg bone fractures. The recommended method in this research was Harris corner detector method. Before identified, the object was firstly in pre-processing such collecting data, grayscale and cropping image. The research result was Harris corner detector method could identify leg bone fractures with 70% accuracy.